2023
DOI: 10.3390/cryst13071054
|View full text |Cite
|
Sign up to set email alerts
|

Specific Features of Formation of Electron and Hole Trapping Centers in Irradiated CaSO4-Mn and BaSO4-Mn

Abstract: Spectroscopic and thermoactivation methods were used to study the processes of accumulation of electron and hole trapping centers and energy transfer of electronic excitations to impurities in CaSO4-Mn and BaSO4-Mn. It is shown that electronic trapping centers are created during the excitation of an anionic complex as a result of charge transfer from O2−→SO42− to closely spaced anionic complexes SO42− in CaSO4 and BaSO4. In CaSO4 and BaSO4, energy transfer from the host to impurities occurs at the moment of ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the studies by authors [20,21], the mechanisms for the accumulation of intrinsic and impurity electron-hole-trapping centers were explored in both pure and Mn 2+ -activated CaSO 4 and BaSO 4 . It was demonstrated that intrinsic SO 3− 4 − SO − 4 and impurity Mn + − SO − 4 trapping centers form as a result of free electrons localizing on the SO 2− 4 anion and Mn 2+ impurities, through the reactions SO 2− 4 + e − → SO 3− 4 and Mn 2+ + e − → Mn + .…”
Section: Introductionmentioning
confidence: 99%
“…In the studies by authors [20,21], the mechanisms for the accumulation of intrinsic and impurity electron-hole-trapping centers were explored in both pure and Mn 2+ -activated CaSO 4 and BaSO 4 . It was demonstrated that intrinsic SO 3− 4 − SO − 4 and impurity Mn + − SO − 4 trapping centers form as a result of free electrons localizing on the SO 2− 4 anion and Mn 2+ impurities, through the reactions SO 2− 4 + e − → SO 3− 4 and Mn 2+ + e − → Mn + .…”
Section: Introductionmentioning
confidence: 99%